APPLICATION OF FACTORS TO INCREASE THE DURABILITY OF MODIFIED ASPHALT CONCRETE - Akhadjon Akhmedov Urmonjonovich (Journals Park Publishing, 2022)
This article shows the application of durability improvement of modified asphalt concrete made from "Kraton D1186" polymers and the addition of SFM "SP-OEP" surface-forming additives during long-term water saturation, which is influenced by the main parameters of asphalt concrete related to frost, corrosion and cracking resistance. passed.
Keywords: temperature, corrosion, humidity, crack resistance, freezing, water resistance